2023
DOI: 10.1136/heartjnl-2022-321943
|View full text |Cite
|
Sign up to set email alerts
|

Habitual physical activity levels of adults with heart failure: systematic review and meta-analysis

Abstract: ObjectiveTo conduct a systematic review and meta-analysis to quantify habitual physical activity (PA) levels of patients with heart failure (HF) and assess the quality of reporting of device-assessed PA.MethodsEight electronic databases were searched up to 17 November 2021. Data on the study and population characteristics, method of PA measurement and PA metrics were extracted. A random-effects meta-analysis (restricted maximum likelihood with Knapp-Hartung SE adjustment) was conducted.ResultsSeventy-five stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“… 51 In contrast, our participants had a baseline of ≈5000 steps, representative of the step count observed in patients with HF in other studies. 52 Nonetheless, this explanation seems less plausible, as our subgroup analysis revealed that patients with step counts above the median tended to benefit more from the intervention compared with those below the median. Another explanation could be the COVID-19 pandemic, which significantly affected patients’ activity levels and could have confounded the results.…”
Section: Discussionmentioning
confidence: 82%
“… 51 In contrast, our participants had a baseline of ≈5000 steps, representative of the step count observed in patients with HF in other studies. 52 Nonetheless, this explanation seems less plausible, as our subgroup analysis revealed that patients with step counts above the median tended to benefit more from the intervention compared with those below the median. Another explanation could be the COVID-19 pandemic, which significantly affected patients’ activity levels and could have confounded the results.…”
Section: Discussionmentioning
confidence: 82%